Pemberdayaan Pemuda melalui Wirausaha Sablon Kaos untuk Meningkatkan Perekonomian Desa Bangsring Kecamatan Wongsorejo Kabupaten Banyuwangi - Siti Nur Afifatul Hikmah; Anyes Lathifatul Insaniyah (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2023)
Bangsring as a village has a million tourism potentials that should be developed. In this case, researchers are interested in the potential development activities contained in Bangsring Village. This assistance aims to develop and revive the Bangsring village t-shirt screen printing community which has experienced a vacuum. Therefore, this activity was carried out to rebuild the spirit of Bangsring youth. This mentoring method uses the Asset Based Community Development (ABCD) approach. Through this method, Bangsring screen printing t-shirt activities can run well. It even has economic value that is quite attractive to UMKM actors. With this in mind, this mentoring activity can benefit the community, especially Bangsring Village, in developing UMKM products.